The seer of shadows - Avi, 1937- (New York, NY : HarperCollins Publishers, 2008)
In New York City in 1872, fourteen-year-old Horace, a photographer's apprentice, becomes entangled in a plot to create fraudulent spirit photographs, but when Horace accidentally frees the real ghost of a dead girl bent on revenge, his life takes a frightening turn.
Grades 3-7.
A Junior Library Guild selection
edited hb 2015-06-16
Keywords: Ghosts -- Juvenile fiction; Photography -- History -- Juvenile fiction; Revenge -- Juvenile fiction; Swindlers and swindling -- Juvenile fiction; Ghosts -- Fiction; Horror stories; Photography -- History -- Fiction; Revenge -- Fiction; Swindlers and swindling -- Fiction; New York (N.Y.) -- History -- 1865-1898 -- Juvenile fiction; New York (N.Y.) -- History -- 1865-1898 -- Fiction